2015
DOI: 10.1371/journal.pone.0118436
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Causes for Decreased Levels of Glutathione in Individuals with Type II Diabetes

Abstract: Tuberculosis (TB) remains an eminent global burden with one third of the world’s population latently infected with Mycobacterium tuberculosis (M. tb). Individuals with compromised immune systems are especially vulnerable to M. tb infection. In fact, individuals with Type 2 Diabetes Mellitus (T2DM) are two to three times more susceptible to TB than those without T2DM. In this study, we report that individuals with T2DM have lower levels of glutathione (GSH) due to compromised levels of GSH synthesis and metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
112
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(137 citation statements)
references
References 33 publications
8
112
2
2
Order By: Relevance
“…GSH levels appear to be diminished by at least two different mechanisms: direct effects of glucose and insulin on GSH synthesis, and by the consumption of a cofactor required for GSH regeneration from GSSG (i.e., NAPDH) via the polyol pathway. Similar to what occurs in HIV-positive subjects, in diabetics, GSH deficiency in the PBMCs accounts for their impaired ability to control infection caused by M. tb and other intracellular bacterial pathogens via a defect in IL-12 production (Tan et al, 2012;Lagman et al, 2015). Interestingly, aldose reductase activity appears to be regulated by S-glutathionylation providing an additional link between GSH and these disease states (Cappiello et al, 2001;Giral et al, 2008).…”
Section: Th1/th2 Immune Responses and The Role Of Gsh In Human Patholmentioning
confidence: 93%
“…GSH levels appear to be diminished by at least two different mechanisms: direct effects of glucose and insulin on GSH synthesis, and by the consumption of a cofactor required for GSH regeneration from GSSG (i.e., NAPDH) via the polyol pathway. Similar to what occurs in HIV-positive subjects, in diabetics, GSH deficiency in the PBMCs accounts for their impaired ability to control infection caused by M. tb and other intracellular bacterial pathogens via a defect in IL-12 production (Tan et al, 2012;Lagman et al, 2015). Interestingly, aldose reductase activity appears to be regulated by S-glutathionylation providing an additional link between GSH and these disease states (Cappiello et al, 2001;Giral et al, 2008).…”
Section: Th1/th2 Immune Responses and The Role Of Gsh In Human Patholmentioning
confidence: 93%
“…However, it was observed that the increment in the GSH level advances the action against MTB infections. Moreover, cytokines accountable for MTB infection at cellular level, such as TNF- α , IL-1 β , IL-2, IFN- γ , and IL-12, were found to be altered in DM type 2 individuals; interestingly the augmented level of some immunosuppressive cytokines such as IL-10 was also found in the same individual [44]. Even short chain fatty acid could also be responsible for the enhanced susceptibility of MTB where the effect of butyrate on different immunologic condition of cytokines in PBMC of diabetic individuals was studied.…”
Section: Dm Enhances Susceptibility To Tb Infectionmentioning
confidence: 99%
“…Glutamin-sistein ligazın katalitik alt birimi, katalitik aktivite için sistein ve glutaminin bağlanmasından sorumludur. Glutamin-sistein ligazın düzen-leyici alt birimi ise GCLC'nin etkisini artırır (32,33).…”
Section: Glutatyonunclassified